Urban Poverty Reduction in Batam City: Dimensions of Poverty and Policy Response - pratiwi, Diah Ayu; Ani, Fauziah; Meri Enita Puspita Sari (Human Sustainability Procedia, 2022)
This study discusses urban poverty reduction in Batam. Researchers focus on the dimensions of poverty and policy response. In analyzing the characteristics of urban poverty in Batam, the researchers used the dimensions of income, education, health, security, and ability to participate as indicators. Meanwhile, in looking at the government’s policy response to tackling poverty, the researcher uses a poverty alleviation model, namely providing direct assistance, providing social services, empowering human resources, providing basic assets for the poor, and creating and developing markets. The results show that the income dimension plays an important role in the characteristics of urban poverty in Batam. The policy response carried out by the government is more inclined to the economic approach than the community empowerment approach.